2018
DOI: 10.1080/0142159x.2018.1463087
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate teaching tools for clinical teaching encounters: A critical scoping review and thematic analysis to establish definitional clarity

Abstract: Applicability of DTTs to specific alternate settings should be considered in context, and appropriately designed justification studies are warranted to demonstrate efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 213 publications
1
17
0
1
Order By: Relevance
“…19,41 Several strategies can be used to make on-shift teaching more efficient. 6,32,60 The teacher could ask the learner to briefly review the literature for a given illness and then teach this back to the instructor and other learners. 23,30,31,37,60,61 This will instill lessons of lifelong learning, such as strategies for accessing the literature on shift, and provides an opportunity for the learner to develop advanced knowledge on a specific topic while freeing up the teacher to see the patient.…”
Section: Environmental and Timing Considerationsmentioning
confidence: 99%
“…19,41 Several strategies can be used to make on-shift teaching more efficient. 6,32,60 The teacher could ask the learner to briefly review the literature for a given illness and then teach this back to the instructor and other learners. 23,30,31,37,60,61 This will instill lessons of lifelong learning, such as strategies for accessing the literature on shift, and provides an opportunity for the learner to develop advanced knowledge on a specific topic while freeing up the teacher to see the patient.…”
Section: Environmental and Timing Considerationsmentioning
confidence: 99%
“…These items were combined with a model for delivering feedback (Rudolphet al, 2006;Rudolph, Raemer and Shapiro, 2013)to develop the deliberate teaching tool, dubbed the Concise Regular Assessment and Feedback for Teaching and learning (CRAFT) framework ( Figure 1). The three phases of the CRAFT framework are based on a previously described instructional structure (Irby, 1992), utilised by almost 75% of subsequently described deliberate teaching tools (Sidhu and Edwards, 2018).The design did not prohibit opportunistic teaching of other clinical teaching points as they emerged during a case. While the framework advocated using a specific feedback delivery model, supporting material stated that participant specialists were free to use any feedback model familiar to them in order not to discourage feedback provision.…”
Section: Results/analysismentioning
confidence: 99%
“…Clinical training traditionally relies on an apprenticeship model that occurs through immersion in the clinical environment without a formal structure or prior planning (Bleakley, 2006), while newer apprenticeship education models describe a process of constructing new knowledge on the foundations of what is already known to the learner (Bleakley, 2006;Taylor and Hamdy, 2013;Morris and Blaney, 2014). Deliberate teaching tools are "frameworks that enable clinicians to have a purposeful and considered approach to teaching encounters by incorporating elements identified with good teaching practice" (Sidhu and Edwards, 2018). No deliberate teaching tool has been designed for or evaluated in clinical anaesthesiology (Sidhu and Edwards, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nebeker et al investigated gender differences in 727 learning objectives generated by 125 residents in consultation with attending surgeons, each learning objective generated prior to a case and classified as either knowledge-based, skill-based, or attitude-based 37. The use of learning objectives for each teaching encounter is recognized as good educational practice and is a feature of many deliberate teaching tools 38. They found that female residents were 1.4 times more likely to select a knowledge-based learning objective over a skill-based one, and when the attending surgeon was female, all residents were more likely to select knowledge (1.6 times) and attitude (2.1 times) over skill 37.…”
Section: Discussionmentioning
confidence: 99%